Need Assessment of Physics Learning Evaluation Course on COVID-19 Pandemic Era in Bloom's Taxonomy Topic - Mukhayyarotin Niswati Rodliyatul Jauhariyah; Wasis Wasis; Titin Sunarti; Woro Setyarsih; Abu Zainuddin; Samsul Hidayat (Berkala Ilmiah Pendidikan Fisika, 2021)
Needs assessment aims to understand the requirements of learning in the COVID-19 pandemic era, the use of online learning platforms, the constraints and solutions offered, the "Merdeka Belajar" curriculum in this course, the challenges and needs in the future. It is an exploratory study for students need on the new learning condition because of the COVID-19 pandemic era. The data gathered from the questionnaire of some lectures and undergraduate programme of physics education students through an online survey also included observation and analysis from various sources. The results show the following facts. It needs online learning with a user-friendly device for students. There are multiple online education platforms based on learning activities, but some students have constraints on internet network stability. Another problem is the need for internet data packages that are not small in the online learning process, especially when using virtual face-to-face platforms. On the other hand, there was a reduction in the semester credit system's weight for the physics learning evaluation course in the "Merdeka Belajar" curriculum. The content of Bloom's taxonomy is quite dense and takes time to understand each level of thinking. So, the future challenge is to develop a learning media that students can use in studying Bloom's taxonomy topic and solve the problem of internet data packages and internet network stability. One alternative solution to learning problems is using learning media in electronic books that students can use offline.